Creating a safe place: SRE teaching as an act of security and identity formation in government schools in Australia. Issue 1 (2nd January 2016) - Gross, Zehavit; Rutland, Suzanne D.
Abstract : This study seeks to analyse the components that contribute to Special Religious Education (SRE) classes in government schools in Australia being considered as a 'safe place' and the ways in which they facilitate an understanding of the students' own religious and cultural identity. Our research focuses on one of the small faiths, Judaism, as a case study through observation of the Jewish SRE/SRI classes in the two largest Jewish population centres, Sydney and Melbourne. Semi-structured interviews were conducted with 90 participants, and classroom observations were undertaken in both cities. This paper draws on Kymlicka's concept of the rights of minority groups in a liberal society and discusses the distinction between thin and thick multiculturalism. Our findings show that the Jewish SRE teachers implemented Jackson's interpretive approach, ensuring that the students' educational experience is meaningful. As a result, they are able to develop their unique identity capital, which is important in a multifaith society to ensure 'thick' multiculturalism. Our argument is that students need to have an understanding of their own particularistic identity, as well as learning to respect other religions.